Synthesis and characterization of palladium(II) and platinum(II) mixed ligand complexes of the type [M(bpozs)2(dppf)]Cl2, bpozs=2-(benzylthio)-5-phenyl-1,3,4-oxadiazole - Rezan A. Saleh; Hikmat A. Mohammad (Zanco Journal of Pure and Applied Sciences, 2021)
Treatment of [PdCl2(dppf)].CH2Cl2 or [PtCl2(dppf)] with two moles of 2-(benzylthio)-5-phenyl-1,3,4-oxadiazole (bpozs) in (ethanol: chloroform) solvents for (2 h) afford [M(bpozs)2(dppf)]Cl2 in good yield. The synthesized ligand and complexes were identified using FT-IR, 1H-NMR, 13C-NMR, 13P-NMR, CHNS analysis, Uv-Visible spectra and conductivity measurements. The physiochemical data indicated that the prepared complexes have square planar geometries and the metal ions coordinate with the ligands through two phosphorous atoms of (dppf) and nitrogen atom of (bpozs).